DETEKSI KAPSUL DAN SLIME PADA BAKTERI PATOGEN YANG DIISOLASI DARI BENIH LELE DUMBO (Clarias gariepinus) - Fadilah, Muhyiatul; Alberida, Heffi; Irdawati, Irdawati (Sainstek : Jurnal Sains dan Teknologi, 2011)
Pathogenic bacterial ability to cause disease is called patoghenicity. Bacteria pathogenicity level stated as virulency. Bacterial virulency is determined by virulency agent, include certain structure of the cell and secrete produced into substrate. Capsul and slime are specific cell structure which act as virulency agent. Capsul and slime presence is able to prevent phagocytosis by host antibody. This study aimed to confirm presence of capsul and slime produced by pathogenic bacterial isolated from Clarias gariepinus. These pathogens are Alcaligenes sp., Bacillus sp., Micrococcus sp., Proteus sp., Pseudomonas sp., and Serratia sp. This is a descriptive study. Observation has been done to detect intense layer arround the cells by using negative staining methode.  Result of study has informed that Alcaligenes sp., Bacillus sp., Micrococcus sp., Proteus sp., Pseudomonas sp., dan Serratia sp., examined do not form capsul and slime.Key words: Capsul and slime, bacterial pathogen, Clarias gariepinus